Formulation and Evaluation of Wax Matrix Fast Dissolving Mini-tablets of Montelukast Sodium - Deshpande, A. H. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: To prepare montelukast sodium mini-tablets that have sweet taste and dissolve quickly, using wax type matrix forming agents such as carnauba wax, rice bran wax, glyceryl monostearate, and polyethylene glycol 4000. Materials and Methods: Mini-tablets were prepared by direct compression technique after the blends of wax matrix formers and drug with other excipients was evaluated for characteristics such as flow properties. The tablets were evaluated for parameters such as thickness, hardness, friability, disintegration time, dissolution time, and mouthfeel. Results and Discussion: The blends of waxes showed satisfactory properties of flow and were directly compressed to tablets with desirable physical properties. The tablets disintegrated within 2 min and had an acceptable mouthfeel. Conclusion: The wax matrix substances can be successfully used for the formulation of mini-tablets with a pleasant taste and mouthfeel.